The Activity of Notika Leaves (Archboldiodendron calosericeum KOBUSKI) Against Tumors Necrosis Factor Alpha (TNF-) Levels in Rats - Nuralifah Nuralifah; Parawansah Parawansah; Fadhliyah Malik; Nining Yulianti (MEDULA (JURNAL ILMIAH FAKULTAS KEDOKTERAN UNIVERSITAS HALU OLEO), 2022)
Inflammation is a response process to tissue injury and infection. The inflammatory response causes the release of pro-inflammatory mediators such as IL-1, IL-6 and TNF-α which are the main cytokines in the acute inflammatory response. Plants that have the potential to be anti-inflammatory are notika leaves (Archboldiodendron calosericeum KOBUSKI). This research was conducted to determine the anti-inflammatory activity of the ethanol extract of notika leaves against the levels of Tumor Necrosis Factor Alpha (TNF-a) in wistar mice. This study used a post test only control group design. Using 5 treatment groups, namely positive control (diclofenac sodium), negative control (NaCMC 0.5%), 100 mg/kgBW extract test group, 200 mg/kgBW extract group and 300 mg/kgBW extract group. In vivo tests were carried out by induction of inflammatory substances, administering preparations and measuring TNF-α levels using the ELISA method. Data were analyzed using the One Way ANOVA test. The results showed that the mean levels of TNF-α in the positive control group (0.475 ng/L), negative control (0.816 ng/L), extract dose 100 mg/kgBW (0.67 ng/L), extract dose 200 mg/kgBW (0.7285 ng/L) and extract dosage of 300 mg/kgBW (0.7785 ng/L). The conclusion obtained is that the ethanol extract of notika leaves has anti-inflammatory activity against the levels of Tumor Necrosis Factor Alpha (TNF-a) in Wistar rats based on the reduction in levels with negative control and the best dose was 100 mg/kgBW.